Contamination level and prevalence of foodborne pathogen Enterobacteriaceae in broiler and backyard chicken meats sold at traditional markets in Surabaya, Indonesia - Ratna Yulistiani,; Praseptiangga, Danar; Supyani,; Sudibya, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aimed to determine contamination level and prevalence of foodborne pathogen Enterobacteriaceae in broiler and backyard chicken meats sold at traditional markets in Surabaya Indonesia. The average of Enterobacteriaceae count of backyard chicken meats (7.61 log10 cfu / g ± 0.62) were significantly higher (P < 0.05) than those obtained from broiler chicken meats (6.14 log10 cfu / g ± 0.81). Overall, the prevalence of Enterobacteriaceae in backyard chicken meats was significantly higher (P <0.05) than broiler chicken meats, Salmonella spp. was the most common isolate recovered from backyard (96.67%) and broiler (81.67%) chicken meats, E. coli (backyard 76.67%; broiler 66.67%), Citrobacter spp., Proteus spp., Yersinia spp., Klebsiella spp., Shigella spp., Enterobacter spp., Serratia spp., Edwardsiella spp. and Morganella spp. Morganella spp. was found only in backyard chicken meats, and not found (0.00%) in broiler chicken meats. The high level of contamination and the prevalence of Enterobacteriaceae in chicken meats are related to poor sanitation and hygiene conditions in the traditional markets of Surabaya, Indonesia.